Identification with management and the organisation as key mechanisms in explaining employee reactions to talent status. (22nd December 2020) - Wikhamn, Wajda; Asplund, Kajsa; Dries, Nicky
Abstract: This study examines how identification with management and the organization explains the relationship between talent status, organizational citizenship behavior towards the organization (OCB‐O) and the supervisor (OCB‐S), and turnover intention. Using archival and survey data ( N = 597), we tested two competing models: a parallel and a serial mediation. Results supported serial mediation of management identification through organizational identification; management identification was the most predictive mediator overall. We also found different exchange dynamics depending on the focus of the identification (management or organization) and their corresponding outcomes (OCB‐S and OCB‐O); OCB‐S was most strongly related to management identification. We contribute to the literature by integrating concepts and assumptions from social identity and social exchange theory, and advancing the understanding about employee reciprocation of symbolic resources such as talent status. Practical implications, in particular about encouraging 'pre‐identification' with management in order to ensure talents' continued extra‐role behavior and retention, are spelled out.